Development of a Pocket Book on Agloanema Plants on Students' Interest in Learning Biodiversity Material - Annisa Arafah; Hasruddin Hasruddin; Khairiza Lubis (Randwick International of Education and Linguistics Science Journal, 2023)
The lack of student interest in learning biology regarding biodiversity, especially the aglaonema plant, is due to insufficient teaching materials and inappropriate use of media, so it is necessary to develop learning media to increase students' interest in learning. The aim of this research is to produce the book product Aglaonema Ornamental Plants to increase interest in studying biology with the theme of biodiversity in students at SMA Negeri 2 Medan. This research is development research or Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The subject of this research is the Aglaonema ornamental plant pocket book, while the object of this research is students' learning interests. The data analysis technique used in this research is quantitative analysis. The results of this research show that from the material expert validation process an average result was 3.35, the language expert validation obtained an average result of 3.7, and the design expert validation obtained a result of 3.5 and the interest in learning questionnaire data obtained 72.97%. or as many as 27 students in the very high category. So it can be concluded that the development product in the form of a pocket book on aglaonema ornamental plants is suitable and effective for use as a companion in learning which can increase students' interest in learning